2006
DOI: 10.2353/ajpath.2006.051161
|View full text |Cite
|
Sign up to set email alerts
|

JAB1 Determines the Response of Rheumatoid Arthritis Synovial Fibroblasts to Tumor Necrosis Factor-α

Abstract: Fibroblast-like synoviocytes (FLSs) of patients with rheumatoid arthritis (RA FLSs) exhibit prosurvival, rather than apoptotic, response to tumor necrosis factor (TNF)-␣ stimulation. Here, we show that JAB1 is a critical regulator of the TNF-␣-mediated anti-apoptosis pathways in RA FLSs. We found that knockdown of JAB1 using small interfering (si)RNA led to restoration of the TNF-␣-induced apoptosis response, reduction of nuclear factor-B activity, delayed degradation of IB-␣, and inhibited phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…This is true particularly for TNFalpha, which does not induce apoptosis in RA-FLS at all but rather promotes proliferation. As demonstrated by the group of John D. Mountz, TNFalpha can induce apoptosis in RA-FLS only, when NFkappaB is inhibited, e.g., by gene transfer of dominant negative IkappaB [25] and recent studies have identified the c-Jun activation domain-binding protein-1 (Jab1) as one further important inhibitor of TNFalpha mediated apoptosis in RA-FLS [24]. While the data for TRAIL have been conflicting [21,23], most recent data suggest that although RA-FLS exhibit an apoptotic response following stimulation with TRAIL, the susceptibility of RA-FLS to TRAIL-induced apoptosis is somewhat lower than to FasL/CD95L and largely depends on the cell cycle (Pundt et al unpublished observation).…”
Section: Ra-fls Are Protected From Receptor-mediated Apoptosis At Mulmentioning
confidence: 97%
See 1 more Smart Citation
“…This is true particularly for TNFalpha, which does not induce apoptosis in RA-FLS at all but rather promotes proliferation. As demonstrated by the group of John D. Mountz, TNFalpha can induce apoptosis in RA-FLS only, when NFkappaB is inhibited, e.g., by gene transfer of dominant negative IkappaB [25] and recent studies have identified the c-Jun activation domain-binding protein-1 (Jab1) as one further important inhibitor of TNFalpha mediated apoptosis in RA-FLS [24]. While the data for TRAIL have been conflicting [21,23], most recent data suggest that although RA-FLS exhibit an apoptotic response following stimulation with TRAIL, the susceptibility of RA-FLS to TRAIL-induced apoptosis is somewhat lower than to FasL/CD95L and largely depends on the cell cycle (Pundt et al unpublished observation).…”
Section: Ra-fls Are Protected From Receptor-mediated Apoptosis At Mulmentioning
confidence: 97%
“…Although RA-FLS have been demonstrated to express a variety of death inducing surface receptors of the TNFreceptor family such as Fas/CD95 [13], TRAIL-R1 and -R2 [21][22][23] and also TNFR1 [24], multiple lines of evidence indicate that they are relatively resistant also to receptorinduced apoptosis. This is true particularly for TNFalpha, which does not induce apoptosis in RA-FLS at all but rather promotes proliferation.…”
Section: Ra-fls Are Protected From Receptor-mediated Apoptosis At Mulmentioning
confidence: 99%
“…This speculation is supported by recent data indicating that CSN5 is dysregulated in both different types of cancers and aging-related diseases. 5,[34][35][36][37][38][39] Although we have identified a role for the CSN5 subunit of COP9 in TLR-mediated innate immune responses of macrophages, further research is needed to understand why KO of CSN5 leads to preferential prevention of activation of p38 and Erk1/2 but not of NF-B in macrophages and also how these activities impinge on the overall physiology of the organism. …”
mentioning
confidence: 98%
“…A pGEX-CSN5 construct was generated by PCR amplification from the pcDNA3-CSN5 template, 19 using forward primer 5Ј-TTGTTGGGATCCATGGCGGCGTCCGGGAGC-GGTAT-3Ј and reverse primer 5Ј-CTATTAGAATTCTTAA-GAGATGTTAATTTGATT-3Ј (BamHI and EcoRI restriction sites are underlined). The pGEX-CSN5 construct was generated by ligating annealed primers in-frame into BamHI-EcoRI digested pGEX-2T vector (Amersham Biosciences).…”
Section: Csn5 Plasmid Dna Constructsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] The CSN core is composed of eight subunits (CSN1-8), 20 and associates with different types of proteins including kinases, ligases, and adaptor proteins. CSN is also related structurally and architecturally to the lid subcomplex of the 26S proteasome that mediates degradation of ubiquitin-conjugated proteins.…”
mentioning
confidence: 99%